2022
DOI: 10.3390/biology11070992
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Wearing Different Surgical Face Masks during High-Intensity, Short-Rest Resistance Exercise on Cardiorespiratory and Pulmonary Function and Perceptual Responses in Weightlifters

Abstract: This study investigated the effect of wearing a typical surgical mask (SM) or a three-dimensional (3D) SM (3DSM) during whole-body, high-intensity, short-rest resistance exercise on cardiorespiratory, respiratory, and perceptual comfort responses in weightlifters. Twenty elite weightlifters (6 women and 14 men; age = 24.1 ± 4.9 years; height: 167.45 ± 7.60 cm; body mass = 76.48 ± 19.86 kg) who participated in this study performed 3 resistance exercise sessions in a randomized order: (1) without a mask (NM), (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…Some studies have investigated the effects of face masks in acute exercise and for healthy people, and either no or only minor effects have been reported [3][4][5][6][7][8]. Also, during high-intensity resistance training in elite athletes, no negative mask effects were detected [9]. However, for sedentary people, Umutlu et al [10] reported negative impacts during aerobic exercise with masks, while for end-stage lung disease patients, no negative mask effects were found during a 6 min walking test [11].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have investigated the effects of face masks in acute exercise and for healthy people, and either no or only minor effects have been reported [3][4][5][6][7][8]. Also, during high-intensity resistance training in elite athletes, no negative mask effects were detected [9]. However, for sedentary people, Umutlu et al [10] reported negative impacts during aerobic exercise with masks, while for end-stage lung disease patients, no negative mask effects were found during a 6 min walking test [11].…”
Section: Introductionmentioning
confidence: 99%